IDENTIFICATION OF PHYSIOLOGICAL AND PSYCHOLOGICAL CHANGES DURING MENOPAUSE IN BIREUEN DISTRICT, ACEH PROVINCE - Irma Fitria; Dewi Maritalia; Herrywati Tambunan (UNIVERSITAS AIRLANGGA, 2023)
Background: Menopause is a physiological condition in women where the end of the reproductive period due to the cessation of the menstrual cycle for 12 consecutive months naturally. During menopause, the production of the hormones oestrogen and progesterone by the ovaries decreases and stops, thus causing changes in the hormonal system in the body that can affect physiological changes in the body as well as psychological changes and will have an impact on the woman's next life. Method: This study aims to identify physiological and psychological changes experienced by women during menopause. The research method is descriptive survey research, the population is all menopausal women who live in Bireuen Regency. The sampling technique used random sampling which was taken based on the Slovin formula totalling 392 respondents. The research instrument was a questionnaire distributed to respondents from 11 August to 05 September 2023 during the Elderly Posyandu at the Puskesmas. Data processing and analysis were carried out univariately for each variable of physiological changes and psychological changes using descriptive static tests. Result: The results of the study for physiological changes showed that the majority of respondents experienced difficulty sleeping, visual disturbances, had heart disease, did not experience respiratory problems, experienced changes in appetite, did not experience urinary disorders, experienced skin changes, experienced joint pain, experienced heat on the face. In psychological changes, they experience mood swings, feel tired and lack of enthusiasm and experience memory impairment. Conclusion: It is suggested that it is necessary to provide special support and attention to women in menopause so that they can go through menopause comfortably and happily so that it will reduce the level of dependence on others.